Foreign Experience in The Formation of Intellectual Abilities of Primary School Pupils - Qodirova Sarvinoz Odil qizi (Genius Journals, 2022)
In our society, our young people with developed intellectual abilities, independent thinking, initiative and self-improvement are clearly visible in many areas. As these young people expand, it is important that they develop the basic concepts. An elementary school student's thinking is unique. This is characterized by the fact that it has not yet developed skills in various forms of thinking. Of course, this creates certain difficulties in teaching. In primary school, children acquire the logical thinking skills mentioned. This article discusses ways to develop the intellectual abilities of primary school students with the help of different methods and methodology which have been mentioned, analyzed and discussed in this article
Keywords: Intellectual development; primary education system; compulsory education; methodology